Peningkatan Hasil Belajar IPS Materi Tumbuhnya Semangat Kebangsaan Melalui Model Cooperative Script Peserta Didik Kelas VIII B SMP Negeri 2 Mertoyudan Semester 2 Tahun Pelajaran 2021/2022 - Zumrotul Islamiyah, Siti (Faculty Of Education, 2022)
One of the problems in learning social sciences is the low ability of students to develop an understanding of a concept or phenomenon in social life due to the limited knowledge of students which results in low learning outcomes. The achieved purposes of this study are 1) To describe the improvement of social sciences learning outcomes in terms of the growth of the national spirit in class VIII B students of SMP Negeri 2 Mertoyudan in the 2021/2022 academic year; 2) To describe the behavioral changes that accompany learning the material for the growth of an enthusiastic nationality in class VIII B students of SMP Negeri 2 Mertoyudan in the 2021/2022 academic year through the Cooperative Script learning model. This research is a classroom action research using the Kemmis & Mc. Taggart. The research subjects were 32 students of class VIII B SMP Negeri 2 Mertoyudan. Sources of research data were obtained from qualitative data in the form of teacher and student activity data and quantitative data in the form of student learning outcomes test data. Data analysis used descriptive qualitative and quantitative descriptive methods. The results of the first cycle research obtained that 23 students who completed individually with classical completeness were 72%. Meanwhile the results of the second cycle of research increased with the number of completed students individually which was 28 students with a percentage of completeness of 87.5%. Based on the results of this study, learning using the Cooperative Script learning model can improve the learning outcomes of class VIII B students of SMP Negeri 2 Mertoyudan in the 2021/2022 academic year.